(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2023)
In this article, the importance of the role of demographic policy in ensuring economic stability and security in Uzbekistan is examined in detail. The article analyzes the measures taken by the government of Uzbekistan to maintain sustainable population growth, employment levels and the quality of the workforce. It also examines the relationship between demographics and economic aspects such as the labor market, investment and social protection.